Effects of Halal social media and customer engagement on brand satisfaction of Muslim customer: Exploring the moderation of religiosity. Issue 6 (18th November 2019) - Shah, Syed Alamdar Ali; Sukmana, Raditya; Fianto, Bayu Arie; Ahmad, Muhammad Ali; Usman, Indrianawati Usman; Mallah, Waqar Ahmed
Abstract : Purpose: The purpose of this research is to examine the factors that affect brand satisfaction of a Muslim customer who is making purchases from selling outlets on social media. Design/methodology/approach: The study used a new mechanism of sampling for research studies relating to social media which. Further, we used hierarchical regression to analyze the moderation effects of religiosity. Findings: The authors' findings suggest that religiosity has moderation effects on the relationship between halal social media and brand satisfaction of a Muslim customer and even higher moderation effects on relationship between customer engagement and brand satisfaction of a Muslim customer. Research limitations/implications: The respondents of this research are completely unknown as the data has been collected from google-docs link sharing arrangement. Practical implications: This study identifies factors that need to be focused on winning the brand loyalty of a Muslim customer. Originality/value: This study provides a new sampling methodology to be used for the purpose of studies related to social media, which has been labeled as "social-media disguised snow ball sampling". Further, this study is one of the few studies in the area of "halal social media".